Bronchiectasis The EMBARC Manual (Springer International Publishing, 2018)
This book presents state of the art knowledge and practice in the rapidly developing field of bronchiectasis not due to cystic fibrosis (referred to below simply as bronchiectasis). The focus is especially on diagnosis and existing and emerging therapies, but the book also covers a wide range of other key topics, from pathophysiology, histopathology, and immunology through to pulmonary rehabilitation, nursing care, and management in primary care and pediatric settings. While bronchiectasis was formerly regarded as an "orphan" disease, international data reveal an increase in its prevalence in recent years. Accordingly, there has been renewed interest in the disease, resulting in more clinical research and the development of new treatments. The impact of bronchiectasis on healthcare systems is substantial and it has a clear attributable mortality. In covering all aspects of the disease, this book will be of interest to respiratory, internal medicine, and infectious disease fellows and specialists, final-year medical students, and nurses and physiotherapists. The authors are leading experts and chairs of the steering committee of EMBARC, the first truly international bronchiectasis network. .